Fisher & Paykel Appliances : fitting in to Haier's global innovation system - Zamborsky, Peter; Turner, Paramita (London : SAGE Publications Ltd, 2017)
This case study explains how Haier, a major global appliance maker from China, managed its acquisition of New Zealand's Fisher & Paykel Appliances (F&PA), especially in terms of its innovation strategies. The case provides insights into the international innovation systems of both companies with a particular focus on their European operations. Investment motives, cross-border learning, collaboration strategies, and global innovation management are analyzed. The lessons from the case are more widely applicable to other companies active in international acquisitions and innovation worldwide. In particular, it underscores how the growth in world class companies from emerging markets is fortified by sophisticated interactions with more traditional players from developed countries. Haiers acquisition of F&PA was part of its innovation strategy and allowed them to grasp an opportunity and use it to create and introduce new ideas, processes, or products. The case looks at how this acquisition may influence the business processes of F&PA to maximize their innovation and their success.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Fisher & Paykel Appliances Holdings; Haier (Corporation); Electronic industries -- China -- Case studies; Electronic industries -- New Zealand -- Case studies; International business enterprises -- China -- Case studies; International business enterprises -- New Zealand -- Case studies; Strategic planning -- China -- Case studies; Strategic planning -- New Zealand -- Case studies